(untitled) (Revista de Artes Marciales Asiáticas, 2020)
Over the last few decades, there has been a resurgent interest in New World martial art traditions. The bulk of the attention has focused on African and African diasporic traditions. Many well-researched books and articles have resulted from this focus. Yet, there is much less interest regarding other combative modalities brought to the shores of the New World. For centuries immigrant communities have brought with them sophisticated combative systems that persist to this day. As part of a broader hoplological project, this article seeks to identify and document the diverse armed combative systems still extant and practiced in South America and the Caribbean that have not transformed into solely institutionalized sports or recreational pastimes. With few exceptions these arts continue to be taught, practiced, and used in a variety of informal situations to ensure one’s property or public reputation or as part of an economic strategy in the informal economy. At times paralleling and overlapping these more pragmatic goals, these arts also persist as a way of preserving older cultural moralities, ethics, and forms of masculinity.